Downregulation of microRNA-182-5p contributes to renal cell carcinoma proliferation via activating the AKT/FOXO3a signaling pathway - Xu, Xin (BioMed Central, 2014)
BACKGROUND: Emerging evidence has suggested that dysregulation of miR-182-5p may contribute to tumor development and progression in several types of human cancers. However, its role in renal cell carcinoma (RCC) is still unknown. METHODS: Quantitative RT-PCR was used to quantify miR-182-5p expression in RCC clinical tissues. Bisulfite sequencing PCR was used for DNA methylation analysis. The CCK-8, colony formation, flow cytometry, and a xenograft model were performed. Immunohistochemistry was conducted using the peroxidase and DAB methods. A miR-182-5p target was determined by luciferase reporter assays, quantitative RT-PCR, and Western blotting. RESULTS: miR-182-5p is frequently down-regulated in human RCC tissues. Epigenetic modulation may be involved in the regulation of miR-182-5p expression. Enforced expression of miR-182-5p in RCC cells significantly inhibited the proliferation and tumorigenicity in vitro and in vivo. Additionally, overexpression of miR-182-5p induced G1-phase arrest via inhibition of AKT/FOXO3a signaling. Moreover, FLOT1 was confirmed as a target of miR-182-5p. Silencing FLOT1 by small interfering RNAs phenocopied the effects of miR-182-5p overexpression, whereas restoration of FLOT1 in miR-182-5p -overexpressed RCC cells partly reversed the suppressive effects of miR-182-5p. CONCLUSIONS: These findings highlight an important role for miR-182-5p in the pathogenesis of RCC, and restoration of miR-182-5p could be considered as a potential therapeutic strategy for RCC therapy.